Evaluation of the Clinical use of Metformin or Pioglitazone in Combination with Meloxicam in Patients with Knee Osteoarthritis; using Knee Injury and Osteoarthritis outcome Score - Mohammed M. Mohammed; Kassim J. Al-Shamma; Nizar A. Jassim (College of Pharmacy University of Baghdad, 2017)
Osteoarthritis is the most prevalent arthritic disease and a leading cause of disability. The pathogenesis of osteoarthritis involves multiple etiologies, including variable degree of synovial inflammation. Metformin and pioglitazone could potentially reduce the levels and activity of inflammatory mediators. This may consider as a new therapeutic approach added to the current used drugs in an attempt to decrease the pain, inflammation, and improve daily activity and quality of life in patients with knee osteoarthritis. This study designed to evaluate the clinical utility of using metformin or pioglitazone as anti-inflammatory agents in combination with non-steroidal anti-inflammatory drugs (NSAID) of selective type of cyclooxygenase-2 (COX-2) inhibitor, meloxicam, in the treatment of knee osteoarthritis (OA). Randomized, double blinded clinical study was performed on 98 patients who have symptomatic and radiologic evidence of painful OA of the knee (57 patients only completed the study). Patients were allocated into three groups, group (A); 20 patients treated with meloxicam (15mg/day) alone, group (B); 20 patients treated with metformin (1000mg/day) + meloxicam (15mg/day) and group (C); 17 patients treated with pioglitazone (15mg/day) + meloxicam (15mg/day). The treatment was followed for 12 weeks through measurement of the clinical effects of drugs each 7 days, using the Knee Injury and Osteoarthritis Outcome Score (KOOS) system. The results showed that metformin or pioglitazone, when used in combination with NSAID resulted in significant improvement in the components of KOOS, higher than that produced by meloxicam when used alone. In conclusion, administration of metformin or pioglitazone as adjuvant therapy to NSAID, meloxicam, in OA patients produced very well characterized analgesic and anti-inflammatory activities, and improves the therapeutic profile of meloxicam. Keywords: Metformin, Pioglitazone, Osteoarthritis, Knee injury, KOOS.